Reflections on reflection: Supporting employability learning in the higher education context - Anna Richards; Andrea Reid (Journal of Teaching and Learning for Graduate Employability)
Graduate employability remains a key talking point in higher education despite the contested nature of the construct and the myriad of factors that influence an individual’s capacity to gain employment. Universities are still positioned to produce graduates who can contribute to society and the economy through work. Students are similarly responsible for developing the knowledge and capabilities that will meet employer expectations and assure a successful career. This development process often involves students engaging in reflective practice. This paper reports on the efficacy of a structured, written reflective process implemented across an Australian research-intensive institution to support students to learn from experiences to develop their employability. Our study found value in the use of a formalised, stepwise approach to reflective thinking that helps students make and express meaning from learning opportunities. The findings suggest, however, that attempting to shoehorn the untidy business of reflective thinking into a standard linear approach does present some challenges. Despite these challenges, our examination of a sample of reflections using our process showed evidence of reflective thought. We found alignment with the experiential learning theories that framed the creation of our reflective process in the students’ expressions of their meaning-making endeavours. Our findings strengthen our advocacy of an anchor for reflective thought in a personally meaningful experience and the use of prompts around effect and action to guide students learning.